2020
DOI: 10.1021/acsapm.0c00979
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Zinc Carboxylate Species in Oil Paint Ionomers

Abstract: Oil paint binding media are complex polymer networks that harbor populations of metal ions. Understanding of the reactivity of these metal ions, often closely linked to paint degradation, is crucial to support paintings conservation efforts. By developing a spectrum fitting approach for the analysis of Fourier transform infrared spectra, we have studied in detail how the molecular structures of zinc carboxylate species in oil paint ionomers change in the lifetime of a painting. It was found that high ZnO pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 34 publications
4
53
0
Order By: Relevance
“…[ 9 , 13 , 33 , 50 , 59 , 69 , 74 , 89 , 94 , 95 , 96 ] Many studies have demonstrated how IR spectroscopy can provide essential information both regarding the behaviour of metal ions in oil paint and their surrounding molecular environment. [91] …”
Section: How To Detect Metal Soapsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 9 , 13 , 33 , 50 , 59 , 69 , 74 , 89 , 94 , 95 , 96 ] Many studies have demonstrated how IR spectroscopy can provide essential information both regarding the behaviour of metal ions in oil paint and their surrounding molecular environment. [91] …”
Section: How To Detect Metal Soapsmentioning
confidence: 99%
“…After the crystallisation and zinc soaps formation, two different structures may be observed (one that optimizes zinc carboxylate coordination ‐type A‐ and one that optimizes fatty acid chain packing ‐type B). [ 55 , 91 , 100 ] Depending on the nature of fatty acids present in the system, geometry A or B are preferred. The former geometry formed when short‐chain, dicarboxylic and unsaturated fatty acids are present while the latter when long‐chain saturated often all four types are simultaneously present in a sample, an overlap of the signals can occur fatty acids are present.…”
Section: How To Detect Metal Soapsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the organic molecular composition of an oil paint layer evolves from polyunsaturated triglycerides to a significantly more complex system, whose composition evolves over years, even centuries, entailing the simultaneous presence of free fatty acids, free dicarboxylic acids, mono-, di- and triglycerides, and cross-linked fractions 2 , 3 , 5 , 7 , 10 , 11 , 13 17 . In addition, when metal soaps are formed, carboxyl moieties are bound to metal cations, in variable proportions depending on the age of the paint, the environmental conditions 18 , 19 , and the nature of the pigment 20 , leading to the formation of free metal soaps and ionomer-like networks 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Free fatty and dicarboxylic acids can be determined qualitatively and quantitatively by GC-MS based techniques 11 , 13 , 31 , 32 , HPLC-MS 14 and flow injection analysis coupled with ESI-MS 33 . Metal soaps have been extensively studied with spectroscopic techniques which are helping to distinguish between free metal soaps and those belonging to the ionomeric network 12 , 20 , 21 , 23 , 30 , 34 40 . Free metal soaps may also be determined by using mass spectrometry 32 , 41 .…”
Section: Introductionmentioning
confidence: 99%